B-Group vitamin production by lactic acid bacteria - current knowledge and potential applications - Leblanc, Jean Guy Joseph (2011)
Although most vitamins are present in a variety of foods, human vitamin deficiencies still occur in many countries, mainly because of malnutrition not only as a result of insufficient food intake but also because of unbalanced diets. Even though most lactic acid bacteria (LAB) are auxotrophic for several vitamins, it is now known that certain strains have the capability to synthesize water-soluble vitamins such as those included in the B-group (folates, riboflavin and vitamin B 12 amongst others). This review article will show the current knowledge of vitamin biosynthesis by LAB and show how the proper selection of starter cultures and probiotic strains could be useful in preventing clinical and subclinical vitamin deficiencies. Here, several examples will be presented where vitamin-producing LAB led to the elaboration of novel fermented foods with increased and bioavailable vitamins. In addition, the use of genetic engineering strategies to increase vitamin production or to create novel vitamin-producing strains will also be discussed. This review will show that the use of vitamin-producing LAB could be a cost-effective alternative to current vitamin fortification programmes and be useful in the elaboration of novel vitamin-enriched products.